Censornet: The Competing Ideals of Censorship and Cyberspace - McCarthy, M (Victoria University of Wellington Law Review, 1997)
This article examines current measures, both domestic and international, which attempt to censor the emerging technologies of the Internet. The attenuated application of traditional legislative regimes to such technologies is currently limited only by inherent prosecutorial discretion. Recent legislative mechanisms seek to address the anomaly, only to replicate assumptions concerning the modes and sites of liability. The increasing technological convergence of media necessitates more informed and instructive approaches to the institutions and objectives of censorship, a process which involves international considerations.